Adsorption Behaviour of Pymetrozine by Four Kinds of Biochar from Aqueous Solution - Liqiang Cui; Jinlong Yan; Guixiang Quan; Cheng Ding; Tianming Chen; Qaiser Hussain (Adsorption Science & Technology)
A laboratory experiment was performed to investigate the potential of biochar (BC) as an adsorbent for removing pymetrozine from aqueous solution. The adsorption data were well described by Langmuir isotherm, with maximum pymetrozine adsorption capacities of 13.8, 20.6, 11.0 and 18.8 mg g −1 for bush-, wheat straw-, peanut- and corn-derived BC in a single solution at 25 °C, respectively. The functional groups of BCs were –NH (1628.25 cm −1 ), –OH (3443.78 cm −1 ), –PO 4 (1089.2 cm −1 ) and –C–Cl (769.23 cm −1 ), which were responsible for binding pymetrozine. The adsorption capacity of BC was increased by 7.2–106.4% at different solution pH (1, 3, 5 and 7). The removal efficiency increased with the addition of BCs and over 70% pymetrozine removal was observed upon addition of up to 8 g l −1 . The rate of pymetrozine adsorption was fast, with 50–80% of the adsorption occurring in the first 120 minutes, followed by a much slower approach to equilibrium. The ΔG° values decreased (increasingly negative) from −165.3% to 235.9% at 298 K compared with 318 K for the adsorption of pymetrozine onto different BCs in a single solution. The study results indicate that plant residue- or agricultural waste-derived BC can act as an effective surface sorbent, but their ability to treat mixed waste streams needs to be carefully evaluated on an individual basis.